Enhancing Cross-Culturally Communicative Skill through Collaborative Online International Learning - Agustinus Rustanta; Mych Chua; Grace Anika; Patricia Nathania; Fudan Putri Theresia Tambunan (Jurnal Ilmu Komunikasi dan Bisnis, 2024)
In today's interconnected world, Collaborative Online International Learning (COIL) programs have emerged as valuable platforms for facilitating cross-cultural communication and fostering global competence among students. However, the effective exchange of ideas and meaningful collaboration in such programs can be hindered by various cross-cultural communication challenges. The purpose of this study is to describe cross-cultural communication skills in the distance learning process. This research was conducted using a qualitative approach with data in the form of interview results. Data were obtained from interviews, Focus Group Discussion (FGD), and observations. The informants are the distance learning participants of Collaborative Online International Learning (COIL). The number of informants is determined purposively according to the needs of this study. The results of the study obtained a tendency that distance learning participants felt interested and challenged by this distance learning model. They are interested because this learning is one of the variations of learning. It is challenging because they are in an environment where they learn to use English as an instructional language. With this learning model, students can improve their cross-cultural skills without having to spend a lot of money and in an easy way.